The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7759/cureus.29792
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Anxiety With Hypertensive Crisis: A Cross-Sectional Study From a Hospital Setting in Karachi, Pakistan

Abstract: IntroductionHypertension, a leading risk factor for cardiovascular death, has been closely linked with depression and anxiety. The aim of this study was to examine the association of depression or anxiety with hypertensive crisis in patients and also see if the association is affected by age group or gender. This was carried out in a hospital setting. MethodsThis cross-sectional study was conducted between July 2019 and March 2022 on 290 patients admitted to the Aga Khan University Hospital (AKUH), Karachi, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Some studies used a validated questionnaire to assess adherence, while others measured antihypertensive medication levels in blood or urine. The reason for non-adherence in patients with a hypertensive crisis could be that they are more likely to have anxiety as reported in our previous study that 59% of patients with hypertensive crisis had anxiety, although the association could not reach statistical significance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used a validated questionnaire to assess adherence, while others measured antihypertensive medication levels in blood or urine. The reason for non-adherence in patients with a hypertensive crisis could be that they are more likely to have anxiety as reported in our previous study that 59% of patients with hypertensive crisis had anxiety, although the association could not reach statistical significance [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that anxiety and depression may be related to the rise of BP while other studies showed a transient sympathetic mediated rise in BP due to stress (72)(73)(74)(75). Though more studies are required to undoubtedly establish a direct relationship between stress, anxiety, and depression with hypertension, stress-whether emotional, social, cultural, or occupational-may lead to several illnesses including the development of hypertension (76).…”
Section: Experiencing Stress Throughout the Life Coursementioning
confidence: 99%